PI3K class IB controls the cell cycle checkpoint promoting cell proliferation in hepatocellular carcinoma - Dituri, F.; Mazzocca, A.; Lupo, L.; Edling, C.; Azzariti, A.; Antonaci, S.; Falasca, Marco; Giannelli, G. (2012)
Alterations of the cell cycle checkpoint frequently occur during hepatocarcinogenesis. Dysregulation of the phosphatidylinositol-3-kinases (PI3K) signaling pathway is believed to exert a potential oncogenic effect in hepatocellular carcinoma (HCC), ultimately promoting tumor cell proliferation. However, the impact of PI3K on cell cycle regulation remains unclear. We used a combined loss- and gain-of-function approach to address the involvement of p110? in HCC cell proliferation, apoptosis and the cell cycle. We also investigated the correlation between p110? and Ki-67 in 24 HCC patients. Finally, we analyzed the expression levels of p110? and cell cycle regulators in HCC tissues. We found that PI3K class IB, but not class IA, is required for HCC cell proliferation. In particular, we found that knock-down of p110? inhibits cell proliferation because of an arrest of the cell cycle in the G0-G1 phase. This effect is associated with an altered expression of proteins regulating the cell cycle progression, including p21, and with an increased apoptosis. By contrast, we found that ectopic expression of p110? promotes HCC cell proliferation. Tissues analysis performed in HCC patients showed a positive correlation between the expression of p110? and Ki-67, a marker of proliferation, and, even more importantly, that p21 expression is up-regulated in HCC patients with a lower p110? expression. Our results emphasize the role of p110? as a promoter of HCC proliferation and unveil an important cell cycle regulation function of this molecule. Copyright © 2011 UICC.